Core outcome sets for spinal and associated limb, trunk, abdomen or pelvic pain: A systematic review - Tim Noblet; Carol Li; Richard Newsham-West; David Walton; Alison Rushton (PLoS ONE, 2025)
Background Spinal pain is a significant global health issue, affecting millions and ranking as one of the leading causes of disability worldwide. Despite the wide scope of research conducted on spinal and associated pain, the lack of standardised core outcome measures poses challenges for comparing and synthesising research data. Core Outcome Sets (COSs) are intended to harmonise assessment and facilitate comparison across studies. This review aimed to identify, map, and examine published core outcome sets (COSs) designed for the assessment of spinal pain—including cervical, thoracic, lumbar—and spinal-related limb, trunk, abdomen, or pelvic pain. It also sought to synthesise consistent outcome domains across these COSs, categorising them by anatomical region and measurement type, including patient-reported, physical, biological, psychological, social, and environmental measures. Methods This systematic review followed PRISMA guidelines and was registered with PROSPERO. A comprehensive literature search of 13 electronic databases and grey literature sources was conducted from 2000 to April 2025. Two independent reviewers assessed study eligibility and quality using predefined criteria. Data extraction was performed to identify core outcome domains, and a thematic analysis was conducted to categorise domains based on anatomical regions, patient-reported outcomes, performance measures, and biopsychosocial factors. Results Thirteen studies met inclusion criteria, addressing core outcome sets for cervical (n = 4), thoracolumbar (n = 1), and lumbar (n = 8) spinal regions. Patient-reported outcome measures were the most frequently recommended outcome type. The most commonly endorsed domains were physical function n = 9 (100%), pain intensity n = 8 (88.9%), participation in work or daily activities n = 7 (77.8%), and disability n = 6 (66.7%). However, few studies incorporated psychological, social, environmental, or physiological domains, highlighting critical gaps in the multidimensional assessment of spinal pain. Conclusion This systematic review identified key domains in current use and significant gaps in biopsychosocial and biological measurement. Findings will support researchers, clinicians, and policymakers in selecting appropriate outcomes for spinal pain research and practice. A Delphi study to develop an internationally agreed “Essential Universal Set” for spinal pain, inclusive of multidimensional biopsychosocial domains, is a sound next step.